Mollisol: Biological Characterization under Zero Tillage with Different Crops Sequences - Silvestro, Luciana (2017)
Zero tillage practices have a direct effect on soil microbial communities modifying soil productivity and sustainability. The crop sequences used can change the aforementioned properties, too. In this study, we evaluated the effect of crop sequences under zero tillage management on soil biological and chemical properties including vertical distribution of soil organic carbon, soil basal respiration, and dehydrogenase, acid phosphatase, and urease activity along a seasonal year and at different soil depths. The sequences included in this study were: (I) Single crop per year (sunflower-wheat-sorghum-soybean); (II) Mixed agriculture/livestock with pastures, without using winter or summer forages (wheat sorghum/soybean-canola-pasture); (III) Winter management (wheat-canola-barley-late soybean); (IV) Mixed with annual feed crop (wheat-oat/Vicia sativa- soybean or sunflower), and (V) Intensive management (wheat-barley-canola, with alternation of soybean or late soybean). Soil organic carbon decreased with increasing depth, depending on sequences (Pseq×depth= 0.0173). Soil basal respiration was higher in the 0-5 cm layer than in the 10-20 cm layer of the topsoil irrespective of the crop sequences (Pdepth= 0.0062). Dehydrogenase, acid phosphatase and urease activity were affected by crop sequences, sampling season, and depth. Mixed sequences (sequences II and IV), including perennial pastures or annual feed crop could favor dehydrogenase and phosphatase activity. Sequences with cover crops (sequences II and IV) could favor microbial activity and, therefore, improve soil quality.